Healing effects of quercetin on full thickness epidermal thermal injury in Wistar rats - Efthalia Gouma; Yannis V Simos; Ioannis Verginadis; Anna Batistatou; Spyridon Karkabounas; Angelos Evangelou; Vasilios Ragos; Dimitrios Peschos (International Journal of Phytomedicine, 2016)
There are many difficulties in treatment and management of a thermal injury, especially after topical application of the therapeutic agents. Quercetin is a well known agent, which exhibit antioxidant, anti-inflammatory and angiogenic functions. This study was carried out to investigate the effect of quercetin on thermal injury healing in a rat model. Ninety female Wistar rats were used. Animals were inflicted with a reproducible full-thickness burn and randomized into three groups to receive no treatment (control group, CG), local application of a quercetin solution (quercetin group, QG) as well as application of the glyceryl trioctanoate, the solvent used to prepare the solutions (solvent group, SG). The size and healing progress of each wound was recorded and evaluated by means of clinical evaluation, planimetry and histological examination on days 0, 3, 6, 12, 21, and 31. Even though a significantly accelerated wound healing and faster re-epithelialization was recorded in QG compared to other groups, quercetin application failed to lead to a rapid healing of full-thickness burns. The use of quercetin could to be an alternative treatment of burn wounds but further research is needed to evaluate the effective doses for speeding up healing time.